Discovery and validation of biomarkers to guide clinical management of pneumonia in African children - Huang, H; Ideh, R; Gitau, E; Thézénas, M; Jallow, M; Ebruke, B; Chimah, O; Oluwalana, C; Karanja, H; Mackenzie, G; Adegbola, R; Kwiatkowski, D; et al. (Oxford University Press, 2014)
Background. Pneumonia is the leading cause of death in children globally. Clinical algorithms remain suboptimal for distinguishing between severe pneumonia from other causes of respiratory distress like malaria, and between bacterial pneumonia and pneumonia from others causes such as viruses. Molecular tools could improve diagnosis and management.Methods. We conducted a mass spectrometry-based proteomic study to identify and validate markers of severity in 390 Gambian children with pneumonia (N=204) and age, sex and neighborhood-matched controls (N=186). Independent validation was conducted on 293 Kenyan children with respiratory distress (238 with pneumonia, 41 with P. falciparum malaria and 14 with both). Predictive value was estimated by the area under the receiver operating characteristic curve (AUROC).Results. Lipocalin-2 (Lpc-2) was the best protein biomarker of severe pneumonia (AUROC: 0.71 [95% CI, 0.64-0.79]) and highly predictive of bacteremia (AUROC 78% [95% CI, 64-92%]); pneumococcal bacteremia (AUROC 84% [95% CI, 71-98%]); and ‘probable bacterial etiology’ (AUROC: 91% [95%CI 84-98]). These results were validated in Kenyan children with severe malaria and respiratory distress who also met the WHO definition of pneumonia. The combination of Lpc-2 and haptoglobin distinguished bacterial versus malaria origin of respiratory distress with high sensitivity and specificity in Gambian children (AUROC: 99% [95%CI 99-100%]) and in Kenyan children (AUROC: 82% [95% CI, 74-91%]).Conclusions. Lpc-2 and haptoglobin can help discriminate the etiology of clinically defined pneumonia, and could be used to improve clinical management. These biomarkers should be further evaluated in prospective clinical studies.